Evaluation of Anthropometric Indices for Screening Hypertension Among Employees of Mizan Tepi University, Southwestern Ethiopia - Dereje R; Hassen K; Gizaw G (Dove Medical Press, 2021)
Rahel Dereje,1,2 Kalkidan Hassen,1 Getu Gizaw1 1Department of Nutrition and Dietetics, Institute of Health Science, Faculty of Public Health, Jimma University, Jimma, Ethiopia; 2School of Public Health, College of Medicine and Health Science, Mizan Tepi University, Mizan Aman, EthiopiaCorrespondence: Rahel Dereje Email raheldereje3@gmail.comBackground: Globally, hypertension is becoming a serious problem affecting the health and wellbeing of the adult population. Anthropometric indices like body mass index (BMI), waist circumference (WC), and waist-to-hip ratio (WHR) have long been utilized to screen hypertension; in contrast, other evidence indicates the superior utility of waist-to-height ratio (WHtR) to screen hypertension. There are inconclusive results from different studies done in different settings regarding the best screening index for hypertension. In addition, there is a paucity of information on the evaluation of anthropometric indices for screening hypertension in the study area. Therefore, this study evaluates the utility of anthropometric indices for screening hypertension among Mizan Tepi University employees, southwestern Ethiopia.Methods: An institution-based cross-sectional study was conducted among Mizan Tepi University employees. A gender-based stratified simple random sampling technique was used to select 585 employees. Logistic regression analysis was conducted to assess the association between anthropometric indices and hypertension. Receiver operating characteristic curve (ROC) was employed to evaluate anthropometric indices for screening hypertension, and optimal cutoff points were also developed based on Youden index (sensitivity + specificity - 1) and presented with sensitivity, specificity, positive predictive value (PPV), and negative predictive values (NPV).Results: The overall prevalence of hypertension was 20.9%, which was 22.5% in males and 18.7% in females. Among males, WHtR, WHR, and BMI were significantly associated with hypertension, while, in females, only BMI was associated with hypertension. WHtR had a higher screening ability for hypertension followed by WC in both sexes. For males, the cutoff point for WHR, WC, BMI, and WHtR for screening hypertension was 0.897, 85.17cm, 24.6kg/m2, and 0.51, respectively. In females, the cutoff point developed for screening hypertension for WHR, WC, BMI, and WHtR were 0.92, 85.67cm, 24.8kg/m2, and 0.52, respectively.Conclusion: The waist-to-height ratio was found to be the best obesity index to screen hypertension than BMI, WC, and WHR. The finding supports the use of WHtR for screening hypertension in resource-limited settings.Keywords: obesity, WHtR, BMI, WHR, WC